The outcomes of transcatheter aortic valve replacement in a cohort of patients with end‐stage renal disease. Issue 7 (4th March 2016) - Szerlip, Molly; Kim, Rebeca J.; Adeniyi, Tokunbo; Thourani, Vinod; Babaliaros, Vasilis; Bavaria, Joseph; Herrmann, Howard C.; Anwaruddin, Saif; Makkar, Raj; Chakravarty, Tarun; Rovin, Joshua; Creighton, Don; et al.
Abstract : Objectives: To examine whether transcatheter aortic valve replacement (TAVR) is a safe and effective treatment option for aortic stenosis in patients with end‐stage renal disease (ESRD). Background: Patients with ESRD undergoing surgical aortic valve replacement have an operative mortality approaching 20% and a 10‐year survival of approximately 12%. We investigated whether TAVR is a more reasonable option. Methods: This is a multicenter, retrospective study of all patients with ESRD who underwent TAVR in 8 institutions between 12/2011 and 02/2013. Demographic characteristics, mortality, major, and minor complications were evaluated. Outcomes were stratified by operative approach. Results: Forty‐three patients with a mean age 76.2 ± 11.0 years and a mean STS predicted risk of mortality of 15.53 ± 8.70% underwent TAVR. Mean duration of dialysis was 45.2 ± 52.3 months (median 29.5 months). Transfemoral (TF) TAVR was performed in 31/43 (72.1%), transapical in 11/43 (25.6%), and transaortic in 1/43 (2.3%). Operative mortality was 14.0% (6/43) with TF mortality 6.5% (2/31) and 33.3% (4/12) in non‐TF patients. Six‐month mortality was 11/43 (25.6%: 16.1% TF, 50.0% non‐TF). Complications included stroke in 2.3% (1/43) and life‐threatening or major bleeding in 14.0% (6/43). Discharge to another healthcare facility was 27.0% (10/37). Readmission within 30 days of procedure for any cause was 18.9% (7/37). Conclusions: Patients with ESRD who undergo TAVR are at high risk for mortality and complications. TAVR outcomes are comparable to but not substantially better than those with SAVR. Transfemoral TAVR seems to be at least as safe and effective as the current standard SAVR in patients undergoing aortic valve replacement. © 2016 Wiley Periodicals, Inc.